Estimasi Efisiensi Teknis Perbankan Indonesia Berbasis Stochastic Frontier Analysis - Mulyana, Rahmat; Achsani, Noer Azam; Andati, Trias; Maulana, Tubagus Nur Ahmad; Pratama, Alfin Yoga (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2022)
Indonesia's banking efficiency is still a concern for many stakeholders, especially with the challenges to compete in the era of the ASEAN Economic Community. This study estimates the value of banking technical efficiency using Stochastic Frontier Analysis and shows that the numbers have not improved significantly in the last ten years. From the time-varrying SFA model it appears that the national banking industry experienced a decline in efficiency from 2007-2009, most likely due to the impact of the world financial crisis but improved again in 2010 and so on at a certain average level until 2016. Hausman test results from three SFA models show that the time-invariant model is statistically better so that it can be concluded that banking efficiency has stagnated over the past decade (2007-2016). The measurement result of Indonesian banking technical efficiency in that period have an average value of 0.677.